Protection Orders in South Africa: The Effectiveness of Implementation and Enforcement for Victims of Gender-based Violence - Ncube, Mongiwa Pamela (Department of Public Law, 2022)
This study's focus is aimed at determining the effectiveness of a protection order (PO) in South Africa obtained against gender-based violence (GBV). This legal instrument's function is to protect victims against further violation from the perpetrator. The Domestic Violence Act 116 of 1998 (DVA), grants victims the right to a PO. However, the enormous number of GBV cases in South Africa continues to increase. This alludes to South Africa's lack of adequate implementation and enforcement, in contradiction of its constitutional obligation to protect. The continued prevalence of GBV requires an investigation of whether preventative legal instruments, such as the PO, are fulfilling their purpose and the judicial implications of failure to provide protection. This study examined the international human rights law obligation South Africa has to promote and fulfil the right to protection against GBV. Extensive existing research confirms that victims of GBV, statistically, are likely to be female. It was vital to examine obligations that South Africa has assumed through regional legal mechanisms, as they similarly guide implementing protective measures against GBV. The national legal framework was revisited and the provisions in the DVA were reassessed to give a clear indication of the PO processes. The outcome of the study revealed that South Africa's PO process provisions in the DVA, have enabled South Africa to comply with its international, regional and domestic obligation to safeguard victims against GBV. However, there are glaring shortcomings in the implementation of the PO machinery. Law enforcement and prosecuting authority were found to be major contributors to these shortcomings. The research found that several of these essential service providers are challenged with full adherence to the provisions regarding the granting of the PO. These shortcomings have the effect that, in practice, South Africa has failed to comply with its obligations to international and regional human rights treaties and the South African Constitution. This study recommends ways in which POs can be applied more successfully in South Africa. The study suggests revised and strengthened legal processes, and more effectively informed intervention strategies.